Encephalopathy in Acute Leukaemia Associated with Methotrexate Therapy. Issue 253 (June 1972) - Kay, H. E. M.; Knapton, P. J.; O'Sullivan, J. P.; Wells, D. G.; Harris, Ruth F.; Innes, Elizabeth M.; Stuart, J.; Schwartz, F. C. M.; Thompson, Eileen N.
Abstract : Seven patients are described in whom dementia developed during treatment with methotrexate for meningeal leukaemia. The patients presented with confusion, tremor, ataxia, irritability, and somnolence. There were major epileptic fits in two cases and in one case there was progression to coma and death. Necropsy findings in the latter showed infarcted areas in the temporal and parietal lobes, with no evidence of active leukaemic disease or of viral encephalitis. The condition has not responded to radiotherapy and no positive evidence of viral encephalitis has been obtained. On the other hand, when treated with folinic and folic acid the deterioration has been arrested and there has been some improvement; thus the condition appears to be due to methotrexate. The occurrence of so many cases within the past year of a condition not previously described is probably attributable to the introduction of intensive cytotoxic therapy directed against meningeal leukaemia.